Price Reactions to Dividend Initiations and Omissions: Overreaction or Drift? - MICHAELY, RONI; THALER, RICHARD H.; WOMACK, KENT L. (Journal of Finance, 1995)
ABSTRACT This article investigates market reactions to initiations and omissions of cash dividend payments. Consistent with prior literature we find that the magnitude of short‐run price reactions to omissions are greater than for initiations. In the year following the announcements, prices continue to drift in the same direction, though the drift following omissions is stronger and more robust. This post‐dividend initiation/omission price drift is distinct from and more pronounced than that following earnings surprises. A trading rule employing both samples earns positive returns in 22 out of 25 years. We find little evidence for clientele shifts in either sample.